2002
DOI: 10.1007/s1145-002-0910-6
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and molecular characterization of the Δ6‐desaturase from two Echium plant species: Production of GLA by heterologous expression in yeast and tobacco

Abstract: The synthesis of GLA (delta6,9,12-1-8:3) is carried out in a number of plant taxa by introducing a double bond at the delta6 position of its precursor, linoleic acid (delta9,12-18:2), through a reaction catalyzed by a delta6-desaturase enzyme. We have cloned genes encoding the delta6-desaturase (D6DES) from two different Macaronesian Echium species, E. pitardii and E. gentianoides (Boraginaceae), which are characterized by the accumulation of high amounts of GLA in their seeds. The Echium D6DES genes encode pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…The sphingolipid LCB D 8 desaturases insert a double bond six carbons from the last oxygen-carrying carbon atom of the alkyl chain in the LCBs and this common regio-specificity is also indicative of an apparent paralogous relationship with the D 6 -desaturases (Sperling et al 1998;Napier et al 1999). Whilst several fatty acid D 6 -desaturases have previously been characterised from higher plants, these have all been isolated from the borage family and, as such, display a very high level of sequence identity (Sayanova et al 1997;Garcia-Maroto et al 2002). The (unexpected) identification of an Anemone D 6 -desaturase from the taxonomically unrelated Ranunculaceae provides new information to facilitate the identification of functionally conserved amino acid residues within this higher-plant enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The sphingolipid LCB D 8 desaturases insert a double bond six carbons from the last oxygen-carrying carbon atom of the alkyl chain in the LCBs and this common regio-specificity is also indicative of an apparent paralogous relationship with the D 6 -desaturases (Sperling et al 1998;Napier et al 1999). Whilst several fatty acid D 6 -desaturases have previously been characterised from higher plants, these have all been isolated from the borage family and, as such, display a very high level of sequence identity (Sayanova et al 1997;Garcia-Maroto et al 2002). The (unexpected) identification of an Anemone D 6 -desaturase from the taxonomically unrelated Ranunculaceae provides new information to facilitate the identification of functionally conserved amino acid residues within this higher-plant enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The resultant PCR products of the expected size (»870 bp) were cloned and sequenced. The cloned PCR products isolated from these two Primula species were found to encode polypeptides similar to known fatty acid 6 desaturases from higher plants (Borago oYcinalis, Echium spp, Primula spp, Anemone leveillei; Sayanova et al 1997Sayanova et al , 2003Garcia-Maroto et al 2002;Whitney et al 2003) and also to plant sphingolipid 8-desaturases (Sperling et al 1998;Libisch et al 2000). These partial sequences were used to design 5Ј-RACE primers to amplify the 5Ј ends of two putative desaturases.…”
Section: Isolation Of "Front-end" Desaturases From Two Primula Speciesmentioning
confidence: 99%
“…This gene encodes an acyl-desaturase enzyme catalyzing the synthesis of polyunsaturated fatty acids (Alonso and Maroto, 2000). The functional D 6 -desaturase gene (D6DES) has been cloned from different Macaronesian Echium species (García-Maroto et al, 2002, and Southern blotting analysis revealed a single-copy in their genomes (García-Maroto et al, 2002). The inverse PCR technique allowed us to isolate the D6DES promoter region (D6DES-p) even from distant continental Echium species.…”
Section: Introductionmentioning
confidence: 99%